1979
DOI: 10.1103/physrevlett.43.746
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Moment of Weak Bosons Produced inppandpp¯Collisions

Abstract: Ohio 44106We suggest that the reactions pp~*W yX and pp -*W yX are good candidates for measuring the magnetic moment parameter K in /% = (e/2M w ) (1 +K) . The angular distribution of the W bosons in pp-* W yX is particularly sensitive to this parameter. For the gaugetheory value of K -1, we have found a peculiar zero in d Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
88
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(92 citation statements)
references
References 7 publications
(2 reference statements)
4
88
0
Order By: Relevance
“…Taking the single emission of a photon as the paradigm process, it was shown that the amplitudes can vanish if the other particles participating in the process have the same sign of charge e i . 1 Same-sign charge scattering occurs naturally in high-energy hadron collisions in subprocesses such as ud → W + γ. However similar phenomena can be expected in lepton-hadron collisions, and in particular at HERA in processes such as eq → eq + γ for eq = e + u or e − d. Studies of radiation zeros for these processes at HERA were first performed by Bilchak [11] and more recently by Doncheski and Halzen [12].…”
Section: Introductionmentioning
confidence: 99%
“…Taking the single emission of a photon as the paradigm process, it was shown that the amplitudes can vanish if the other particles participating in the process have the same sign of charge e i . 1 Same-sign charge scattering occurs naturally in high-energy hadron collisions in subprocesses such as ud → W + γ. However similar phenomena can be expected in lepton-hadron collisions, and in particular at HERA in processes such as eq → eq + γ for eq = e + u or e − d. Studies of radiation zeros for these processes at HERA were first performed by Bilchak [11] and more recently by Doncheski and Halzen [12].…”
Section: Introductionmentioning
confidence: 99%
“…It is now more than a dozen years since radiation amplitude zeros were first discovered [1] in the process ud → W + γ [2]. Subsequently, it was shown [3,4,5] that these can arise more generally, originating as the destructive interference of radiation patterns in gaugetheory tree amplitudes for massless gauge-boson emission.…”
Section: Introductionmentioning
confidence: 99%
“…The parton level amplitudes responsible for this process exhibit zeros in the distribution of the scattering angle [3]. The position of the zero depends only on the charge of the quark (no helicity dependence):…”
Section: Radiation Zeros In W γ Productionmentioning
confidence: 99%
“…In the early days of the SM, the processes pp (pp) → W ± + γ + X were suggested for the measurement of the magnetic moment of the W boson, where the radiation amplitude zero was encountered first [3]. We discuss this zero in Section II.…”
Section: Introductionmentioning
confidence: 99%